Climate change in South Kalimantan (Borneo): assessment for rainfall and temperature - Riyan Benny Sukmara; Muhammad Fajrin Wahab; Ariyaningsih (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2022)
A severe flood hit South Kalimantan in 2021. The flood inundated several cities and regions, including Banjamasin City and its surrounding areas in the Martapura Basin. According to data from the National Disaster Management Agency (BNPB), over 20,000 houses were flooded, and over 100,000 people were forced to relocate. Many flood causes are being debated these days, including climate change issues which are triggered by many factors. However, the significant factor indicating its existence is the increase in temperatures. Rising temperature will result in the intensity of the extreme rainfall and the change of its pattern. Due to this background, this study aims to evaluate rainfall and temperature variability as an indicator of climate change in the study area. The Man-Kendall Test is used in this study to analyze a trend analysis and its relationship to rainfall. The results show a temperature trend of 0.2 to 0.3 degrees Celsius over the last two decades. It indicates that climate change has occurred on a local scale. Further, the trend of rainfall and temperature have increased in all selected locations. The annual rainfall over the last 20 years has also increased by roughly 25 mm per annum.